THE TEACHING OF HISTORY UNDER THE ENVIRONMENTAL LIGHTHOUSE:: A CHALLENGE IN FIGHTING PARADIGMS RELATED TO ENVIRONMENTAL HISTORY AND ITS APPLICATION IN THE EDUCATIONAL ENVIRONMENT - Fernando da Silva , Diego (Revista Gênero e Interdisciplinaridade, 2021)
His article aims to foster the debate between conceptions and confluences in the teaching of general history and pedagogical theories in the environmental area, not forgetting the training of students and teaching practice. Thus, the methodology for the elaboration of this article starts from readings of the historiography about his concerns about the environmental theme and its fundamental factors. We realized that the research points to the need for a change in the attitude of everyone involved in society and not Just in the school environment. Hence the importance of clearly evidencing the meanings of the concepts of teaching History, Environmental Education and a way that can be directed and pointed to new paths and new practices.